Diagnostic value of EUS for choledocholithiasis in patients indicated for ERCP - Tan, Phan Nhat; Hien, Pham Nhu; Truong, Le Khac Nhat; Khiem, Nguyen Van; Cuong, Vo Dai Quoc (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Background: To evaluate the diagnostic value of endoscopic ultrasound (EUS) in detecting common bile duct (CBD) stones in patients with indications for endoscopic retrograde cholangiopancreatography (ERCP). Methods: A descriptive study included 41 patients with symptoms suspected of common bile duct stones from January 2022 to May 2023. Results: The mean age of the study group was 64 ± 14.1 years, with 58.5% of patients being 60 years or older. There were 20 male and 21 female patients, with a male-to-female ratio of 1:1.05. 100% of patients presented with abdominal pain. The rate of increased total bilirubin was 58.5%, and the rate of increased direct bilirubin was 73.2%. EUS detected CBD dilation >10mm in 65.9% of patients, stones in 70.7%, stones located in the distal 1/3 of the CBD in 65.5%, and stones >10mm in 62.1%. ERCP evaluation revealed CBD dilation >10mm in 75.6% of patients, a mean CBD diameter of 13.9 ± 4.3mm, and 16 patients (39%) with a single stone. The rate of stones >10mm was 53.6%, with a mean stone size of 11.9 ± 4.9mm. EUS had a sensitivity of 100%, specificity of 92.3%, accuracy of 97.6%, positive predictive value of 96.6%, and negative predictive value of 100% in diagnosing CBD stones, which was superior to ultrasound and CT scan. Conclusion: EUS is an effective, safe, and minimally invasive diagnostic tool for CBD stones.